Procoagulant State in Current and Former Anabolic Androgenic Steroid Abusers - Chang, Simon; Rasmussen, Jon J.; Frandsen, Mikkel N.; Schou, Morten; Johansen, Marie L.; Faber, Jens; Münster, Anna-Marie B.; Sidelmann, Johannes J.; Kistorp, Caroline (Thrombosis and Haemostasis, 2018)
Background Anabolic androgenic steroid (AAS) abusers are considered at increased risk of cardiovascular morbidity and mortality. We hypothesized that current and former AAS abuse would induce a procoagulant shift in the haemostatic balance.Methods Men 18 to 50 years of age were included as current AAS abusers, former AAS abusers or controls. Morning blood samples were collected after overnight fasting. Thrombin generation (lag time, time to peak, peak height, and endogenous thrombin potential [ETP]) and coagulation factor II (prothrombin), VII and X, antithrombin, protein C, free protein S and tissue factor pathway inhibitor (TFPI) were assessed. Groups were compared by ANOVA or Kruskal–Wallis test and probabilities were corrected for multiple comparisons. Associations were evaluated using linear regression models.Results ETP was increased around 15% in current (n = 37) and former (n = 33) AAS abusers compared with controls (n = 30; p < 0.001). Prothrombin and factor X were increased ≥10% in AAS abusers and prothrombin was a predictor of ETP (p < 0.0005). Lag time and time to peak were increased 10 to 30% in current AAS abusers (p < 0.001) and associated with higher concentrations of TFPI, antithrombin, protein C and protein S (p < 0.0005; = 0.005). Multivariate linear regression, with all coagulation inhibitors as covariates, identified TFPI to be independently associated with lag time and time to peak (p < 0.0005).Conclusion Thrombin generation is augmented in current and former AAS abusers, reflecting a procoagulant state, with altered concentrations of coagulation proteins. Prospective studies are needed to clarify whether these findings translate into an increased thrombotic risk in AAS abusers potentially even after cessation.
Keywords: testosterone; substance-related disorders; thrombin; blood coagulation